Peroneal and tibial nerve paralysis after prolonged knee flexion - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Concurrent paralysis of tibial and peroneal nerves due to acute compression is a rare incident. Here, a case of combined peroneal and tibial nerve lesion is reported for the first time ever in the literature which developed acutely due to forced, long-term flexion of the knee joint and failed to show adequate clinical or electrophysiological improvement despite eighteen months of follow-up. A 38-year-old female patient was kept in a fixed position in her bed for about 10 hours in such a way that her left knee was in full flexion. Only partial improvement could be achieved in her neurological symptoms 18 months after the incident and electrophysiological assessment showed limited regeneration. Severe axonal degeneration of both nerves was considered to occur in this patient particularly due to extreme flexion of the knee together with long-term compression. Knee flexion coexisting with long-term compressions may severely damage the peroneal nerve and also the tibial nerve, which is more resistant to compression neuropathy compared to the peroneal nerve. Knee flexion for about 10 hours of compression might have resulted in severe axonal degeneration and affected the prognosis unfavorably.
Keywords: Electromyography; Peripheral nerve injuries; Peroneal neuropathy; Tibial neuropathy